Analysis of the Role of Company Legal Bureaus in Preventing Business Disputes: Structured Interview Approach - Firmansyah Firmansyah; Harjoni Harjoni; Asma Karim; Matteson Niva; Suprio Jaya Putra (Rechtsnormen: Journal of Law, 2024)
Background. Often, conflicts occur in modern business. However, business disputes can be very detrimental to a company financially and to its reputation. Therefore, the role of corporate law firms in preventing and handling business disputes is becoming increasingly important. A corporate law firm can help manage risk and minimize the possibility of disputes. Purpose: The purpose of this research is to study how corporate law firms prevent business disputes. The focus of the research is to understand how they spot potential disputes, create strategies to prevent them, and how they handle disputes that arise. The main aim of this research is to provide deeper insight into how effective the role of corporate law firms is in reducing the risk of business disputes. Method. This research was conducted using a structured interview method. Members of corporate law firms who have relevant knowledge and experience in managing business disputes are the respondents interviewed. Using pre-prepared interview guidelines, interviews are conducted in person or via a virtual platform. Next, qualitative analysis was carried out on the interview data to find patterns, themes and important findings. Results. The research results show that corporate law firms are very important in preventing business disputes. To avoid disputes, respondents create clear contracts, provide training to employees, and monitor changes in legislation. Company authorities also handle disputes using mediation, negotiation, and arbitration. Conclusion. The study found that corporate law firms play a very important role in preventing and handling business disputes. By using the right strategy and proactively involving various parties, corporate law firms can help companies reduce risks and reduce the negative impact of business disputes. Therefore, investment in the development of a corporate law firm can be considered as feasible.